Ontology Development for SysML-Based Energy Harvester Design - Green, Christopher W. (Cybersecurity and Innovative Technology Journal, 2024)
This study presented the development of an ontology for energy harvesting systems, leveraging the Systems Modeling Language (SysML) within a Model-Based Systems Engineering (MBSE). Energy harvesting, which transforms ambient energy into usable electrical power, has gained traction as a sustainable solution for powering low-power devices in applications such as wireless sensors and autonomous systems. This paper explored the diverse sources and components involved in energy harvesting, including transduction mechanisms, power management, and storage, to address the complexity inherent in multi-source energy systems. Using SysML profiles, this study constructs an ontology that formalizes the concepts, relationships, and constraints within the energy harvesting domain, providing a common vocabulary and promoting semantic interoperability among stakeholders. The ontology is developed systematically and structured to facilitate designing and reusing energy harvesting components, supporting increased efficiency and scalability. The results demonstrate how ontology-based design aids in reducing complexity, improving consistency, and fostering collaboration across interdisciplinary teams, offering significant implications for sustainable technology development in energy harvesting applications.